Detecting Oral Cancer: The Potential of Artificial Intelligence - Vats, Rishabh; Rai, Ritu; Kumar, Manoj (Current Medical Imaging, 2022)
Background: Physical inspection is a simple way to diagnose oral cancer. Most cases of oral cancer, on the contrary, are diagnosed late, resulting in needless mortality and morbidity. While highrisk screening populations appears to be helpful, these people are often found in areas with minimal access to health care. In this paper, we have reviewed several aspects related to oral cancer, such as its cause, the risk factors associated with it, India's oral cancer situation at the moment, various screening methods, and the ability of artificial intelligence in the detection and classification purpose. Oral cancer results can be enhanced by combining imaging and artificial intelligence approaches for better detection and diagnosis. Objective: This paper aims to cover the various oral cancer screening detection techniques that use Artificial Intelligence (AI). Methods: In this paper, we have covered the imaging methods that are used in screening oral cancer and, after that, the potential of AI for the detection of oral cancer. Conclusion: This paper covers some of the main concepts regarding oral cancer and various AI methods used to detect it.
Keywords: artificial intelligence